INTEGRASI FMEA DAN ANALISIS SWOT UNTUK PEMILIHAN TINDAKAN KOREKSI PROSES DISTRIBUSI GAS ( STUDI KASUS DI PT. ANEKA GAS INDUSTRI BITUNG ) - Hasyim Pakudu; Agung Sutrisno; Johan S.C. Neyland (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2014)
In gas industry , gas is distributed to customer in the form of gas tube. Empty gas tube from customer will be refilled in filling plant. In its operation, gas distribution is consisting of two activities, namely, delivering gas and picking up empty tube. Based on its historical data, PT. Aneka Gas Industri once in a while facing an operational failures. One of the solution proposed is applying FMEA (Failure Mode and Effect Analisys) method. From its application it is observable some critical and some potential corrective measures. In order to consider internal and external aspects of company operation, SWOT Analisys is integrated into the FMEA method. Results of integrating SWOT Analisys into FMEA Method used to determine Correctional measures taken. Key word : Gas Distribution, FMEA method, SWOT Analisys, correctional measure